Glomerular haemodynamic profile of patients with Type 1 diabetes compared with healthy control subjects. Issue 7 (21st February 2015) - Škrtić, M.; Lytvyn, Y.; Yang, G. K.; Yip, P.; Lai, V.; Silverman, M.; Cherney, D. Z. I.
Abstract Aims To evaluate the glomerular haemodynamic profile of patients with Type 1 diabetes with either renal hyperfiltration (GFR ≥ 135 ml/min/1.73 m2) or renal normofiltration (GFR 90–134 ml/min/1.73 m2) during euglycaemic and hyperglycaemic conditions, and to compare this profile with that of a similar group of healthy control subjects. Methods Gomez's equations were used to derive afferent and efferent arteriolar resistances, glomerular hydrostatic pressure and filtration pressure. Results At baseline, during clamped euglycaemia, patients with Type 1 diabetes and hyperfiltration had lower mean ± sd afferent arteriolar resistance than both those with Type 1 diabetes and normofiltration (914 ± 494 vs. 2065 ± 597 dyne/s/cm5; P < 0.001) and healthy control subjects (1676 ± 707 dyne/s/cm5; p < 0.001). By contrast, efferent arteriolar resistance was similar in the three groups. Patients with Type 1 diabetes and hyperfiltration also had higher mean ± sd glomerular hydrostatic pressure than both healthy control subjects and patients with Type 1 diabetes and normofiltration (66 ± 6 vs. 60 ± 3 vs. 55 ± 3 mmHg; P < 0.05). Similar findings for afferent arteriolar resistance, efferent arteriolar resistance, glomerular hydrostatic pressure and filtration pressure were observed during clamped hyperglycaemia. Conclusion Hyperfiltration in Type 1 diabetes is primarily driven by alterations in afferent arteriolar resistance rather than efferent arteriolar resistance. Renal protective therapies should focus on afferent renal arteriolar mechanisms through the use of pharmacological agents that target tubuloglomerular feedback, including sodium‐glucose cotransporter 2 inhibitors and incretins.